AB0916 Adult-Onset Still's Disease-Experience over Last Five Years. (15th July 2016) - Sagdeo, P.S.; Balakrishnan, C.; Parikh, T.; Mangat, G.; Gc, Y.
Abstract : Background: Adult onset still's disease (AOSD) is a rare systemic inflammatory disorder of unknown etiology seen by a rheumatologist. There is limited data about this disease especially from our country. Objectives: To study the clinical profile of AOSD patients in a tertiary care hospital. Methods: A 5 year (2009–2014) retrospective analysis was done of patients with AOSD (Diagnosed using the Yamaguchi criteria). Their clinical features, laboratory findings at presentation, disease course, treatment and outcomes were analyzed. Results: 14 patients with AOSD according to Yamaguchi criteria were enrolled. The mean age at disease onset was 43.57±16.91 years and the male to female ratio was 4:3. The mean duration of symptoms prior to diagnosis was 2.2 months (range 1–6 months). The most common clinical manifestations were fever (n=14), articular symptoms (n=14), rash (n=7), weight loss (n=7), sore throat (n=4), Lymphadenopathy (n=8), hepatomegaly (n=5), splenomegaly (n=3) and serositis (n=4). Most common joints involved were knee (n=9) followed by wrist (n=7).Neutrophilic leucocytosis was seen in 13, thrombocytosis was seen in 4 patients. Elevated ESR and Ferritin levels were present in all, with a mean of 70±35.18 mm/hr and 3966.35±2988 ng/ml respectively. Hepatic enzymes were elevated in 6. The mean duration of follow up was 18.71±16.99 months. Prednisolone was used in all while methotrexate was used in 12 patients; one patient each required sulfasalazine and cyclosporine. Tender joint and swollen joint counts displayed a progressive reduction on follow up. During treatment, we observed a resolution of fever in all patients. On first follow up mean ferritin levels decreased from 3966.35±2988 to 3018±699 ng/ml. Course of the disease was monophasic in 7 intermittent in 4 and chronic in 3 patients. Conclusions: 1.Fever and joint symptoms were the most common presenting symptom. 2.Steroids and methotrexate was most commonly used for treatment. 3.Majority of patients had clinical improvement with resolution of systemic and joint symptoms. References: Singh S, Samant R, and Joshi VR: Adult onset Still's disease: a study of 14 cases. Clin Rheumatol 2008; 27: pp. 35–39. Kong XD, Xu D, Zhang W, et al: Clinical features and prognosis in adult-onset still's disease: a study of 104 cases. Clin Rheumatol 2010; 29: pp. 1015–1019. Mitamura M, Tada Y, Koarada S, et al: Cyclosporin A treatment for Japanese patients with severe adult-onset Still's disease. Mod Rheumatol 2009; 19: pp. 57–63 Disclosure of Interest: None declared